ADVANTAGES OF IMPLEMENTING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE EDUCATIONAL PROCESS (Global Conference on Multidisciplinary Research and Innovation, 2026)
The rapid development of digital technologies has significantly transformed modern education systems. Among these innovations, artificial intelligence (AI) plays a crucial role in enhancing the quality, accessibility, and efficiency of the learning process. The integration of AI technologies into education enables personalized learning experiences by adapting content, pace, and assessment methods to individual students’ needs and abilities. Intelligent tutoring systems, adaptive learning platforms, and automated feedback tools help identify learners’ strengths and weaknesses, providing targeted support and improving academic outcomes.